Green Sukuk, Energy Poverty, and Climate Change : A Roadmap for Sub-Saharan Africa - Aassouli, Dalal (World Bank, Washington, DC, 2018)
The climate change challenge and the growth of the Islamic finance industry, together with the increase in socially responsible investing, could position green sukuk as a key instrument for financing clean energy and resilient infrastructure projects as well as shorter-term energy efficiency projects. Expansion of a green sukuk market could promote environment-friendly projects and improve livelihoods, helping Islamic finance achieve its moral objectives. A roadmap shows how policy makers could create a green sukuk market in Sub-Saharan Africa.